2019
DOI: 10.1111/jcmm.14327
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell‐conditional medium inhibits H9C2 cardiomyocytes apoptosis via autophagy flux and Wnt/β‐catenin pathway

Abstract: Induced pluripotent stem cell‐derived conditioned medium ( iPS ‐ CM ) could improve cell viability in many types of cells and may be a better alternative for the treatment of myocardial infarction. This study aimed to examine the influence of iPS ‐ CM on anti‐apoptosis and the proliferation of H9C2 cardiomyocytes and investigate the underlying mechanisms. H9C2 cardiomyocytes were exposed to 200 μmol/L hydrogen peroxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(71 reference statements)
2
10
0
Order By: Relevance
“…We measured the Wnt11 in CdM Wnt11 with semi-quantitative Western blotting. The concentration of Wnt11 in CdM Wnt11 was significantly higher than that in CdM GFP , which is consistent with previous reports that Wnt can be secreted from stem cells [45,46]. Therefore, the cardiac injury following ischemia may be, at least partially, due to the loss of non-canonical Wnt signaling.…”
Section: Discussionsupporting
confidence: 90%
“…We measured the Wnt11 in CdM Wnt11 with semi-quantitative Western blotting. The concentration of Wnt11 in CdM Wnt11 was significantly higher than that in CdM GFP , which is consistent with previous reports that Wnt can be secreted from stem cells [45,46]. Therefore, the cardiac injury following ischemia may be, at least partially, due to the loss of non-canonical Wnt signaling.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Leroux et al (48) reported that MScs, via the Wnt4 pathway, improved skeletal muscle fiber regeneration following ischemic injury. Other studies have also demonstrated activation of the Wnt pathway by MScs (55)(56)(57). The present study found that, in the presence of hdPSc-cM, the levels of Wnt/β-catenin pathway-related proteins, including p-GSK-3β and β-catenin, were upregulated.…”
Section: Discussionsupporting
confidence: 72%
“…Substituted 3‐formyl‐2‐quinoline and 3‐formyl‐2‐quinolones, used in our study as starting materials, have been reported for their antimicrobial and antifungal activities. [ 54 ] The literature reports reveal that the quinoline derivatives displayed good antibacterial activity against both Gram‐negative and Gram‐positive bacterial strains [ 55 ] and have immense potential to control methicillin‐resistant Staphylococcus aureus infection. [ 56 ]…”
Section: Resultsmentioning
confidence: 99%